Características anatômicas e ecológicas de casca e madeira de Anadenanthera - Mota, Graciene da Silva (2016)
The bark of Anadenanthera peregrina and Anadenanthera colubrina and Anadenanthera peregrina wood were studied with the following objectives: i) to characterize the anatomy and chemistry of the bark; ii) to analyze the ecological aspect and the structural changes in the bark and wood of Anadenanthera peregrina. These species were sampled in the Fazenda Alvação in the municipality of Coração de Jesus, Northern de Minas Gerais, and at the University campus of the Universidade Federal de Lavras, Southern de Minas Gerais, Brazil. Structurally, the species were similar concerning the presence, morphology and distribution of the bark tissues. Distinctive features not well obvious between the two species. A. peregrina presented bark easily removable from the wood, a large amount of taninniferous cells and greater phellem cell. A. colubrina presented a large amount of sclerified cells in the phloem. The average chemical composition of A. peregrina and A. colubrina bark was, respectively: 8.20% and 7.74% ash; 28.77% and 29.33% total extractives, mainly corresponding to polar compounds soluble in ethanol and water; 18.85%, 18,88% lignin, and 2.40% and 2.58% suberin. Polysaccharide composition showed a predominance of glucose and xylose (82.88% and 81.18%, 8.71% and 8.89% of total neutral monosaccharides, respectively). The ethanol-water bark extracts presented high content of phenolics and considerably differ between A. peregrina and A. colubrina bark, corresponding to, respectively: total phenolics 583.0 and 681.9 mg of gallic acid equivalent/g extract, flavonoids 148.3 and 445.2 mg of catechin equivalent/g extract and tannins 586.9 and 97.5 mg equivalent/g extract catechin. The antioxidant activity corresponded to 237.5 and 268.5 mg Trolox/g extract, respectively. The Anadenanthera bark presents high content of extractives, especially polar extractives, and showed antioxidant activity extractives. The quantitative results of the cellular elements of the bark and wood of A. peregrina showed significant differences in various parameters, as well as variation between specimens from the North and South of Minas Gerais. The correlation matrix of variables including quantitative anatomical characteristics, soil characteristics, height and diameter of the plants, showing that the plants were grouped by region. A. peregrina may adopt different survival strategies concerning safety and efficiency of transport water and solutes by ecological adaptation of the conductive elements of the bark and wood.